2018
DOI: 10.1038/s41409-017-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Better outcome with haploidentical over HLA-matched related donors in patients with Hodgkin’s lymphoma undergoing allogeneic haematopoietic cell transplantation—a study by the Francophone Society of Bone Marrow Transplantation and Cellular Therapy

Abstract: The question of the best donor type between haploidentical (HAPLO) and matched-related donors (MRD) for patients with advanced HL receiving an allogeneic hematopoietic cell transplantation (allo-HCT) is still debated. Given the lack of data comparing these two types of donor in the setting of non-myeloablative (NMA) or reduced-intensity (RIC) allo-HCT, we performed a multicentre retrospective study using graft-vs.-host disease-free relapse-free survival (GRFS) as our primary endpoint. We analysed the data of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…In that study [24], among the patients receiving ISD‐SCT, relapse rate was higher in the minimal residual disease (MRD)‐positive group than in the MRD‐negative group (36% vs. 7%), whereas relapse rates were comparable between the MRD‐positive group and MRD‐negative group among patients who received HID‐SCT (13% vs. 7%); suggesting that HID‐SCT had a stronger graft versus leukemia (GVL) effect than ISD‐SCT [24]. The results from other studies also confirmed the stronger GVL effect in HID‐SCT than in ISD‐SCT [25, 26]. In theory, in HID‐SCT, stronger alloimmune response would be achieved by leukemic cells which express HLA mismatched from donors and result in a decrease in relapse rate.…”
Section: Discussionmentioning
confidence: 99%
“…In that study [24], among the patients receiving ISD‐SCT, relapse rate was higher in the minimal residual disease (MRD)‐positive group than in the MRD‐negative group (36% vs. 7%), whereas relapse rates were comparable between the MRD‐positive group and MRD‐negative group among patients who received HID‐SCT (13% vs. 7%); suggesting that HID‐SCT had a stronger graft versus leukemia (GVL) effect than ISD‐SCT [24]. The results from other studies also confirmed the stronger GVL effect in HID‐SCT than in ISD‐SCT [25, 26]. In theory, in HID‐SCT, stronger alloimmune response would be achieved by leukemic cells which express HLA mismatched from donors and result in a decrease in relapse rate.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasingly used haploidentical SCT (HIDT), HLA-identical sibling donors remain the first choice, though a number of studies have shown that treating patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) using haploidentical donors (HIDs) could achieve comparable outcomes to those who undergoing HLA-matched sibling donor transplantation (MSDT) [3,6,7]. On the other hand, using haploidentical transplants, the graft-versus-leukemia (GVL) effect may be stronger, as mismatches for HLA antigens on leukemic cells would provide allo-immune targets [4,5,[8][9][10][11][12][13]. A recent large European Society for Blood and Marrow Transplantation (EBMT) study indicated that HIDT has a lower incidence of relapse than MSDT for low-risk (HR = 0.83, P = 0.011) and intermediate-risk (HR = 0.85, P = 0.033) hematological malignancies [5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent large European Society for Blood and Marrow Transplantation (EBMT) study indicated that HIDT has a lower incidence of relapse than MSDT for low-risk (HR = 0.83, P = 0.011) and intermediate-risk (HR = 0.85, P = 0.033) hematological malignancies [5]. The better relapse rate with HIDT compared to MSDT has also been observed in patients with lymphomas [8,9]. Our previous studies showed that HIDT is superior to MSDT in terms of a lower relapse rate for patients with high-risk leukemia [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations